Children’s oral health-related quality of life and associated factors: Mid-term changes after dental treatment under general anesthesia - Baghdadi, Ziad D. (J Clin Exp Dent, 2015)
Objectives: This study aimed to document the mid-term effects of comprehensive dental treatment under general anesthesia (DTGA) on parent-assessed children’s oral health-related quality of life (COHRQoL). A second aim was to examine some epidemiological factors associated with COHRQoL and treatment outcome. Study Design: A pretest-posttest design was followed in which parents were surveyed using the Child Oral Health Quality of Life Questionnaire before and 6-9 months after their children (age ranges 3-10 years) underwent DTGA. Some clinical conditions and epidemiological factors were examined to assess their association with COHRQoL and changes resulting from treatment. Results: The clinical sample consisted of 80 children-parent dyads. The effect sizes of change following DTGA were large for both the child impact section and family impact section of the COHRQoL. COHRQoL scores after treatment were comparable or lower than those of a cross-matched group of children with no complaints related to oral health. Child’s age, pain and number of teeth with pulpal involvement showed significant association with both pretreatment scores and change scores. Conclusions: Children’s OHRQoL improved after DTGA as assessed by parents 6-9 months postoperatively. Child’s age, pain and number of pulpally-involved teeth can be used as predictors for COHRQoL and change scores. Key words:Quality of life, children, oral health, reliability.